2021
DOI: 10.3390/nano12010126
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Graphene Oxide Modified with Linear and Branched PEG with Monocytes Isolated from Human Blood

Abstract: Multiple graphene-based therapeutics have recently been developed, however potential risks related to the interaction between nanomaterials and immune cells are still poorly understood. Therefore, studying the impact of graphene oxide on various populations of immune cells is of importance. In this work, we aimed to investigate the effects of PEGylated graphene oxide on monocytes isolated from human peripheral blood. Graphene oxide nanoparticles with lateral sizes of 100–200 nm and 1–5 μm were modified with li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 64 publications
2
9
0
1
Order By: Relevance
“…This is consistent with previous data on other human immune cells from healthy donors. [ 22 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with previous data on other human immune cells from healthy donors. [ 22 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Modification of GO was carried out by covalent bonding of the amino groups of PEG-NH 2 and 8arm-PEG-NH 2 to the surface carboxyl groups of GO. The modification procedure and characterization of these nanoparticles were described in our recent article [ 22 ]. The properties of the nanoparticles are summarized in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Encouragingly, the composite hydrogel promoted bone regeneration without causing obvious inflammation, which might be attributed to the functionalization of GO. GO was reported to cause inflammatory responses while some studies indicated PEG functionalized GO could reduce the production of reactive oxygen species (ROS) and stimulate the secretion of the antiinflammatory cytokine IL-10 (Yue et al, 2012) (Khramtsov et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide nanoparticles with sizes of 100–200 nm (GOs) and 1–5 μm (GOb) (“Ossila Ltd.”, Sheffield, UK) coated with linear (P) and branched (bP) polyethylene glycol (PEG) were used. The procedures for modification and characterization of nanoparticles have been previously described by the authors [ 45 ]. The following particles were used in the study: P-GOs (Ø 184 ± 73 nm), bP-GOs (Ø 287 ± 52 nm), P-GOb (Ø 569 ± 14 nm), and bP-GOb (Ø 1376 ± 48 nm).…”
Section: Methodsmentioning
confidence: 99%